PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA KELAS X SMKN 2 SITUBONDO - Tri Astindari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2021)
This study aims to determine the differences in mathematics learning outcomes between students taught using the Problem Bassed Learning (PBL) model and the discussion method in class X of SMK 2 Situbondo. This research is a quasi-experimental study with the Nonequivalent Control Group Design design. The study population was all students of class X at SMK 2 Situbondo consisting of 7 classes with a total of 206 students. The sample of this study is AK1 class as many as 36 students as the experimental class and AK2 class as many as 31 students as the control class. Data of student learning outcomes in this study were collected by learning outcomes tests. The data analysis technique used was the Independent Sample T-test. The results of the study show that learning using the Probem Bassed Learning (PBL) model can improve the learning outcomes of class X students of SMK 2 Situbondo. This is known based on the average values of the two classes. The group that was taught using the Probem Bassed Learning (PBL) model had an average of 80, while the group taught using the discussion method had an average of 70. To find out the differences in student learning outcomes it can be known based on the result of the Sig. (2-tailed) yaitu 0,033 < 0,05 and the results of the calculation that shows that t count> t table (2,184> 1,997). This means that there are significant differences in the results of mathematics learning between groups of students who take part in learning using the Probem Bassed Learning (PBL) model with groups of students who take part in the learning by discussion method.